JSinAja: Javascript Programming Learning Application (React JS, React Native, Node JS) Mobile Based Using Problem Based Learning Method - Smaragdina, Azhar Ahmad; Nur Susilowati, Risky Cantika; Ahmadi, Rizky; Andriansyah, Yudo Dendy; Md Yunos, Jailani bin (Universitas Negeri Malang, 2023)
This article describes the design of a mobile-based learning application for JavaScript programming using React JS, React Native, and Node JS. This application aims to provide an interactive and engaging learning experience for beginners and advanced JavaScript programming users. This application is designed to cover the basics of JavaScript programming, such as syntax, data types, control structures, functions, and objects. This application also covers more advanced topics, such as asynchronous, functional, and object-oriented programming. The application uses the React JS library for web interfaces, React Native for mobile application development, and Node JS for the backend. The app's user-friendly design has a simple and intuitive interface that guides users through the learning process. This application is also equipped with features such as materials, tutorial videos, and discussions to help users apply their knowledge and test their abilities. In the future, this application is designed to be developed further by adding new modules and features. The app also includes user feedback and analytics to improve the learning experience continuously. This application uses one of the software development methods, namely the waterfall development method, which is based on a structured and sequential sequence of stages. Hopefully, this application will provide a valuable resource for anyone interested in learning JavaScript programming, from beginners to advanced users